Walking the talk? : MNEs transitioning towards a sustainable world - Tulder, Rob van; Grøgaard, Birgitte; Lunnan, Randi (Progress in international business research ;, 2024)
Across the globe, concerns escalate about the effects of greenhouse gas emissions on global climate conditions, implications on global trade from pandemics, and the destruction of ecosystems from the exploitation of limited and non-replaceable global resources. Politicians and businesses alike agree that something must be done, the question is what, how, when, and by whom? What should firms do to reduce their carbon footprint while continuing to secure jobs and profits? When should firms make decisions to transform their businesses given the uncertainty of markets as well as the lack of clear guidance from global institutions? In this volume we ask: Are we actually walking the talk? This volume includes select contributions from the 2022 EIBA conference in Oslo, as well as a number of invited contributions. The book is a tribute to Professor Alain Verbeke who has contributed substantially to the theme of 'walking the talk' in the IB community. The chapters in this volume illustrate a broad spectre of research questions and ways to answer them within the IB community that provide evidence that many types of actors are taking - or can take - steps to actually "walk the talk". The contributions also show, however, that MNEs face considerable challenges to make their ambitions real, which in turn presents a challenge for IB scholarship to develop relevant and robust analytical approaches to cover the transition problems that MNEs face.